Evaluation Of Refrigerating Load And Air Flow Performance In Air Conditioning Unit at Hospital Z - Aulia, Nur Fatowil; Hendrawati, Dwiana; Hanif, Muhammad; Mei H, Baktiyar; Hamim S, Ahmad; Sumarno, F. Gatot; Surindra, M. Denny (Politeknik Negeri Semarang, 2023)
This research was conducted to evaluate air conditioning systems in pharmaceutical warehouses against the ANSI/ASHRAE/ASHE ventilation standards 170 ”“ 2008 and SNI-03-6572-2001. The method used is to calculate the cooling load on the FCU (Fan Coil Unit) using the CLTD (Cooling Load Temperature Difference) method and calculate the External Static Pressure on the ducting system. The analysis is carried out by comparing the results of calculating the FCU requirements with the actual specifications that have been implemented. Furthermore, the measurement results of the existing room air condition are compared with the standards for pharmaceutical warehouse applications. The calculation results show that the pharmaceutical warehouse has a cooling load of 47,472.72 Btu/hr, and has an external static pressure of 123 Pa. While the selected FCU (Fan Coil Unit) has a capacity of 78,771 Btu/hr and a maximum external static pressure of 130 Pa with a rated airflow of 4000 m3/hr. After 9 years of use, it is known that the rated airflow has decreased by around 37% of the FCU capacity. Existing room air conditions obtained the extreme temperature and RH of 23.36 °C and 72%, respectively.